2011
DOI: 10.1111/j.1435-5957.2011.00354.x
|View full text |Cite
|
Sign up to set email alerts
|

On labour market discrimination against Roma in South East Europe

Abstract: Abstract. This paper directs interest on country-specific labour market discrimination Roma The results obtained indicate the presence of labour market discrimination in Albania and Kosovo, but point to its absence in Bulgaria, Croatia, and Serbia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…After accounting for low levels of educational attainment amongst Roma, several studies found persisting labour market inequalities between Roma and non-Roma that are attributed to discrimination. Applying Blinder-Oaxaca decomposition analysis to household surveys, several studies found labour market discrimination against Roma in Bulgaria, Romania and Hungary (Revenga et al 2002), Bulgaria, Kosovo and Serbia (Milcher 2011), Albania and Kosovo (Milcher & Fischer 2011). Applying logistic regression to census data, Kosko (2012) found a "stunningly high level of unexplained difference in employment outcomes" (ibid, p. 437) showing that Romanian Roma with the same level of education attained were more frequently unemployed and in unskilled, low wage employment.…”
Section: Roma the Labour Market And Special Schoolingmentioning
confidence: 99%
“…After accounting for low levels of educational attainment amongst Roma, several studies found persisting labour market inequalities between Roma and non-Roma that are attributed to discrimination. Applying Blinder-Oaxaca decomposition analysis to household surveys, several studies found labour market discrimination against Roma in Bulgaria, Romania and Hungary (Revenga et al 2002), Bulgaria, Kosovo and Serbia (Milcher 2011), Albania and Kosovo (Milcher & Fischer 2011). Applying logistic regression to census data, Kosko (2012) found a "stunningly high level of unexplained difference in employment outcomes" (ibid, p. 437) showing that Romanian Roma with the same level of education attained were more frequently unemployed and in unskilled, low wage employment.…”
Section: Roma the Labour Market And Special Schoolingmentioning
confidence: 99%
“…Using Blinder-Oaxaca decomposition of the Roma vs. non-Roma employment gap (expressed in percentage points) for Western Balkan countries, Robayo-Abril and Millán show that the large employment gap is mostly explained by differences in education. Milcher and Fischer's (2011) findings for Serbia also show that differences in measured characteristics (gender, education, high skills occupation, work experience, or full-time job) and not labour market discrimination against Roma are the dominant reason for the shortfall in the incomes of Roma, although discrimination may also have indirect influence on incomes. On the other hand, O'Higgins (2009) finds that there is a considerable difference in the employment returns to education between Roma and non-Roma in Albania, Bosnia and Herzegovina, Bulgaria, Croatia, North Macedonia, Serbia, Montenegro, Romania, and Kosovo*.…”
Section: Key Determinants Of the Roma Vs Non-roma Gap In Labour Marke...mentioning
confidence: 78%
“…It is known that some migrants from Romania and Bulgaria are motivated by poverty, although the number of migrants who move for this reason is unknown. As well, a small but unknown proportion of migrants are Roma, a minority that is highly discriminated against in Southeast Europe (Masseria et al 2010;Milcher, Fischer 2011;McGarry 2012).…”
Section: Migration From Romania and Bulgariamentioning
confidence: 99%